Pengaruh Mental Accounting, Literasi Keuangan Syariah Dan Love of Money Terhadap Perilaku Keuangan Pelaku Usaha (Studi pada Anggota Koperasi BMT Sarana Wiraswasta Muslim di Kota Malang) - Agusrani Dwi Pratiwi; Anik Malikah; Mohamad Bastomi (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract The financial behavior of entrepreneurs nowadays is becoming increasingly varied and complex, influenced by technological advancements and the instability of global economic conditions. Entrepreneurs' financial behavior plays a crucial role in maintaining healthy and sustainable financial management, especially in cooperative environments like BMT Self-employment facilities Muslim in Malang City. This study aims to examine the impact of mental accounting, Islamic financial literacy, and love of money on the financial behavior of entrepreneurs among members of the BMT Self-employment facilities Cooperative in Malang City, partially. This study employs a quantitative approach with data collection through purposive sampling technique. The sample size reaches 64 respondents, namely active members of the BMT SWM Cooperative in Malang City. Data analysis was conducted using multiple linear regression with SPSS 25 software. The findings of this study indicate that there is no significant influence from the variables of mental accounting and love of money on entrepreneurs' financial behavior. Conversely, the variable of Islamic financial literacy has a significant influence on entrepreneurs' financial behavior among members of the BMT Self-employment facilities Muslim Cooperative in Malang City. Keywords: Mental Accounting, Islamic Financial Literacy, Love Of Money, Financial Behavior Of Business Actors.